Carbon and H2 recoveries from plastic waste by using a metal-free porous biocarbon catalyst. (10th June 2023) - Jin, Yanghao; Yang, Hanmin; Guo, Shuo; Shi, Ziyi; Han, Tong; Gond, Ritambhara; Jönsson, Pär G.; Yang, Weihong
Abstract: Carbon and H2 recoveries from plastic waste enable high value-added utilizations of plastic waste while minimizing its GHG emissions. The objective of this study is to explore the use of a metal-free biocarbon catalyst for waste plastic pyrolysis and in-line catalytic cracking to produce H2 -rich gases and carbon. The results show that the biocarbon catalyst exhibits a good catalytic effect and stability for various plastic wastes. Increasing the C/P ratio from 0 to 2, induce an increase in the conversion rate of C and H in plastics to carbon and H2 from 57.1% to 68.7%, and from 22.7% to 53.5%, respectively. Furthermore, a carbon yield as high as 580.6 mg/gplastic and an H2 yield as high as 68.6 mg/gplastic can be obtained. The hierarchical porous structure with tortuous channels of biocarbon extends the residence time of pyrolysis volatiles in the high-temperature catalytic region and thereby significantly promotes cracking reactions. Graphical abstract: Image 1